Application of Caring Theory to Nursing Care of Women Experiencing Stillbirth. Issue 1 (January 2019) - Nurse-Clarke, Natasha; DiCicco-Bloom, Barbara; Limbo, Rana
Abstract: Purpose: The purpose of this study was to determine the extent to which labor and delivery nurses used the tenets of Swanson's middle-range theory to care for women whose babies were stillborn. Study Design and Methods: A secondary analysis of qualitative in-depth interview data from 20 labor and delivery nurses obtained during a recent grounded theory study was conducted using the directed content analysis method. The five caring processes as described in Swanson's theory were used as a priori codes to conduct the analysis. Results: Nursing care of a woman experiencing a stillbirth included finding a way to connect with her and to understand what she was experiencing (knowing), spending extra time with her (being with), protecting her and preserving her dignity (doing for), providing information and explanations in a clear and methodical manner (enabling), and ensuring that she did not blame herself to facilitate the grieving/healing process (maintaining belief). Clinical Implications: The caring processes outlined in Swanson's theory of caring provide a valuable guide that can be used when caring for women experiencing stillbirth. Abstract : Swanson's theory of caring has application to nursing care of women experiencing stillbirth. In this study, 20 labor and birth nurses share their perceptions of caring for women who have had a stillbirth. Findings suggest the five caring processes described by Swanson enhance the nurse-patient relationship and the bereaved mother's wellbeing.